STRATEGI PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA* - Edy Suandi Hamid; Y. Sri Susilo (Muhammadiyah University Press, 2011)
This research aims to arrange the correct and operational strategies for developing small and medium enterprises (SMEs) in Daerah Istimewa Yogyakarta Province. It also needs to be known and analyzed the SMEs profile. Data used is primary and secondary data. Primary data obtained through field surveys, while secondary data obtained from various publication sources. Method of analysis used is descriptive approach. Associated with the various problems faced by SMEs, there are some strategies needed to overcome them. To develop the SMEs is not only charged to the SMEs themselves but also supported by all stakeholders. The support expected to come from business associations, colleges, related agencies in the area of regency/city governments in DIY. Moreover, government policy is needed to encourage SMEs development. The SMEs development in DIY basically is the acceleration of the SMEs transformation from formation phase to stabilization phase.